2018
DOI: 10.1016/j.nicl.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Brain anomaly networks uncover heterogeneous functional reorganization patterns after stroke

Abstract: Stroke has a large physical, psychological, and financial burden on patients, their families, and society. Based on functional networks (FNs) constructed from resting state fMRI data, network connectivity after stroke is commonly conjectured to be more randomly reconfigured. We find that this hypothesis depends on the severity of stroke. Head movement-corrected, resting-state fMRI data were acquired from 32 patients after stroke, and 37 healthy volunteers. We constructed anomaly FNs, which combine time series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Previous network studies in large-scale brain functional and structural connectivity have also revealed a small-world property of the brain network in healthy human [ 19 , 20 , 40 ]. Previous studies have also found that patients with ischemic stroke demonstrated small-world functional and structural networks [ 22 , 26 , 27 , 41 ]. In the present study, stroke patients also showed small-world properties of their structural networks at both timepoints.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous network studies in large-scale brain functional and structural connectivity have also revealed a small-world property of the brain network in healthy human [ 19 , 20 , 40 ]. Previous studies have also found that patients with ischemic stroke demonstrated small-world functional and structural networks [ 22 , 26 , 27 , 41 ]. In the present study, stroke patients also showed small-world properties of their structural networks at both timepoints.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study using voxel-based morphometry on structural MRI found that gray matter volume in the contralesional SMA was positively correlated with the motor function in patients after local subcortical infarction [ 5 ]. Graphical analysis based on a functional network found that the network connections for areas related to frontoparietal control systems and sensorimotor functions in stroke patients were broken down [ 27 ]. Functional network complexity was correlated with hand and wrist function in stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, some researchers have demonstrated that FCs within the SMN and the interaction between the FPN and the dorsal attention network (DAN) decrease significantly over time in Parkinson's patients, and the longitudinal decline in DAN-FPN interactions corresponds to increased cognitive impairments (44). Furthermore, a recent study on stroke showed that SMN-FPN connectivity is positively associated with the degree of motor and cognitive impairments (45). We speculated that basal ganglia damage might cause SMN-FPN dysfunction, and SBG patients might not be able to effectively combine movement and target information to perform organized and purposeful actions.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have successfully analyzed their domain problem by adopting the NS framework. Transforming the dataset into a network has allowed finding many interesting patterns and results in different areas, like text-mining [36], health sciences [37], stock markets, among many others [38]. In the case of Earth sciences, the network representation has been largely used for analyzing global climate effects and teleconnections [20], [25], wild-fires events [39], anomalies in annual hurricanes events [40], seismic events [41], and continental moisture recycling process [42].…”
Section: Related Workmentioning
confidence: 99%